Tinjauan Hukum Terhadap Upaya Kabupaten Kutai Kartanegara Dalam Mewujudkan Zona Bebas Pekerja Anak (ZBPA) - riniapriyani (Fakultas Hukum Universitas Mulawarman, 2006)
As far as we concern, children are the biggest gift for us. Children will be the country next generation. They are the agent of change of a nation. If there are no educated children, a nation will be just a place with many citizens without any development in it. According to the Convention of ILO 182, there are some worst jobs for children such as slaveries, trafficking, compulsory works and even prostitutes. All abovementioned jobs are not suitable for children and only give a worthless experiences for them and of course can hurt themselves. In order to give education for children and to create the next generation agent of change for Indonesia, Kutai Kartanegara has tried to conduct a program called ‘Free Zone of Child Employee’ which aims to make a zero zone of child employee in Kutai Kartanegara since 2002. Key words: pekerja anak (children employee), zona bebas pekerja anak (free zone of child employee), pekerjaan terburuk (worst jobs).